2016
DOI: 10.1590/1807-1929/agriambi.v20n1p67-71
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of air temperature in a free-stall in the Northeastern semi-arid region of Brazil

Abstract: A B S T R A C TThe knowledge on the spatial variability of climatic attributes and the building of Kriging maps can assist in the design and management of confined animal facilities, by allowing a spatial visualization that is helpful for the planning and control of information from the production environment. The study aimed to characterize the spatial variability of air temperature in a free-stall barn used for dairy cattle confinement located in Petrolina-PE, Brazil, in different seasons and at different ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…where h is the distance between the samples, C 0 is the nugget effect, and a is the interval. The fitted model differs from what has been reported in the relevant literature, specifically, vis-à-vis, research that studied environmental variables in animal facilities that was fitted to the spherical model [14,[29][30][31]. The difference may be due to the sampling grid used in those studies, as well as the environmental effects and/or the experimental design.…”
Section: Data Partition Methods For Validation Of the Modelsmentioning
confidence: 76%
“…where h is the distance between the samples, C 0 is the nugget effect, and a is the interval. The fitted model differs from what has been reported in the relevant literature, specifically, vis-à-vis, research that studied environmental variables in animal facilities that was fitted to the spherical model [14,[29][30][31]. The difference may be due to the sampling grid used in those studies, as well as the environmental effects and/or the experimental design.…”
Section: Data Partition Methods For Validation Of the Modelsmentioning
confidence: 76%
“…Thus, it is observed that the air temperature had low longitudinal variation in the installation, considering that aviary 2 had an adiabatic evaporative cooling system. Gonçalves et al (2016), studied the spatialization of physical variables of the air in rural construction and also observed a low CV for air temperature under semiarid conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Mapas de krigagem relativos ao índice de Temperatura e Umidade (ITU), índice de temperatura de globo negro e umidade (ITGU), índice de Carga Térmica Radiante (CTR) e Entalpia com ventiladores ligados (L) e desligados (D) às 9:00 h no inverno de 2016. Gonçalves et al (2016) também ao estudarem a variabilidade espacial da temperatura do ar de um galpão Free Stall, utilizado para confinamento de bovinos leiteiros, verificaram que o uso da modelagem geoestatística, pode definir áreas especificas que apresentaram valores de temperatura acima do recomendado para o conforto térmico. Dessa forma, pode-se afirmar que a modelagem se torna relevante para o estudo de variáveis climáticas e índices de conforto no interior de galpões para confinamento de gado.…”
Section: Resultsunclassified
“…Neste contexto, a necessidade de entendimento, análise e controle do microclima do ambiente interno nas instalações para confinamento de gado leiteiro é a principal razão para se buscar métodos de modelagem matemática e de representação e processamento computacional. Os métodos de modelagem considerados neste artigo, são os métodos de modelagem geoestatística, como aqueles apresentados por Faria et al (2008), Silva et al (2012) e Gonçalves et al (2016).…”
Section: Introductionunclassified
See 1 more Smart Citation